Дефініція «особистісно-професійна зрілість» у психологічних дослідженнях - Черкашин, А. І.; Cherkashyn, A. I.; ORCID: http://orcid.org/0000-0003-4929-6706 (Право і безпека. – 2017. – № 3 (66). – С. 159–164, 2017)
Наведено результати дослідження дефініції особистісно-професійної зрілості у працях вітчизняних та зарубіжних учених. Визначено, що зрілість є найбільш тривалим періодом онтогенезу, який характеризується тенденцією до досягнення найвищого розвитку духовних, інтелектуальних і фізичних здібностей людської особистості. Указано, що особистісно-професійна зрілість є інтегративним, багатоскладовим психічним утворенням, яке визначає саморозвиток і самодетермінацію особистості у професійній та особистісній сферах власної життєдіяльності. Наголошено, що основними принципами психолого-педагогічної діяльності щодо формування особистіснопрофесійної зрілості майбутнього фахівця є результативність, ефективність, об’єктна орієнтованість змісту педагогічної дії, особистісна орієнтованість, рефлективність і гармонійність.

The author has provided the results of the research on the definition of personal and professional maturity in the works of domestic and foreign scholars. It has been noted that a number of researchers consider the definition of “maturity” as a state of complete development of a personality, complete readiness for something in terms of adult education, formed readiness for the highest development of spiritual, intellectual and physical abilities; the state of the organism that has reached full development; the state to which the body comes at the end of the development period; high development of physiological, intellectual, volitional, moral and social parameters of a person. Other researchers consider maturity as the most prolonged period of ontogenesis, characterized by the tendency to achieve the highest development of the spiritual, intellectual and physical abilities of a human being; deep psychological growth of personality and social maturity. The concept of “personal maturity” is defined by different authors as a characteristic of the state of personality’s development, which manifests itself in a high degree of personal constructive activity and personal functional performance of a person; internal readiness for the implementation of the corresponding act in the life sense of an individual; mastering the meaning of life by a man; the adequacy of self-perception of the I-concept, which reflects the level of self-actualization of an individual; ego-integration, which is achieved by a man in the apogee of his personal development. It has been indicated that personal and professional maturity is an integrative, multidisciplinary mental entity that determines the self-development and self-determination of an individual in the professional and personal spheres of his own life. It has been stressed that the main principles of psychological and pedagogical activity regarding the formation of personal and professional maturity of the future specialist are effectiveness, efficiency, object orientation of the content of pedagogical action, personal orientation, reflectivity and harmony.

Приведены результаты исследования дефиниции личностно-профессиональной зрелости в трудах отечественных и зарубежных учёных. Определено, что зрелость является наиболее длительным периодом онтогенеза, характеризующимся тенденцией к достижению наивысшего развития духовных, интеллектуальных и физических способностей человеческой личности. Указано, что личностно-профессиональная зрелость является интегративным, многосоставным психическим образованием, которое определяет саморазвитие и самодетерминацию личности в профессиональной и личностной сферах жизнедеятельности. Отмечено, что основными принципами психолого-педагогической деятельности по формированию личностнопрофессиональной зрелости будущего специалиста являются результативность, эффективность, объектная ориентированность содержания педагогического воздействия, личностная ориентированность, рефлективность и гармоничность.
Definition of “personal and professional maturity” within psychological research
Дефиниция «личностно-профессиональная зрелость» в психологических исследованиях
Черкашин, А. І. Дефініція «особистісно-професійна зрілість» у психологічних дослідженнях / А. І. Черкашин // Право і безпека. – 2017. – № 3 (66). – С. 159–164.
Cherkashin, A.I. (2017), “Definition of “personal and professional maturity” within psychological research” [“Definitsiia «osobystisno-profesiina zrilist» u psykholohichnykh doslidzhenniakh”], Pravo i Bezpeka, No. 3, pp. 159–164.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; зрілість; особистісно-професійна зрілість; особистість; самоприйняття; самодетермінація; саморозвиток; maturity; personal and professional maturity; personality; self-acceptance; selfdetermination; self-development; зрелость; личностно-профессиональная зрелость; личность; самопринятие; самодетерминация; саморазвитие